THE INFLUENCE OF PRODUCT INNOVATION ON MARKET PERFORMANCE THROUGH THE MEDIATING ROLE OF INNOVATION PERFORMANCE IN UMKM COFFEE SHOPS IN BIREUN REGENCY - Chalirafi; Khairawati (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
performance and competitive advantage in improving marketing performance with the subject of research UMKM Coffeeshop in Bireuen Regency. The stages of the study include: data observation, determining the main problems, activity objectives, literature studies, data collection, data processing, analysis of results, and evaluation of research results. The results of the study show that product innovation has a significant positive effect on marketing performance and innovation performance. Innovation performance has a significant positive effect on marketing performance. Innovation performance has a significant positive effect in mediating product innovation on marketing performance.